Free fire [videorecording (DVD)] - Wheatley, Ben, 1972-; Copley, Sharlto, 1973-; Hammer, Armie, 1986-; Larson, Brie, 1989- (A24 ; Lions Gate Entertainment, 2017)
When two gangs cross paths in a deserted Boston warehouse, a shootout and a game of survival ensues.